Load Carrying Capacity of Hot-Rolled Hybrid Cellular Steel Beams: Experimental Investigations - Sehwail, Mohammad Mufid; Celikag, Murude (Springer Heidelberg, 2022)
The objective of this experimental study was to find out if hybrid cellular beams subjected to bending would lead to increased strength and resistance when compared to their homogeneous counterpart sections. Cellular beams were subjected to mid-span concentrated load to study their load-carrying capacity, failure modes, and load versus vertical and lateral displacements behavior. IPE 330 and IPE 360 hot-rolled parent sections were used to fabricate eight cellular beams in three groups. Groups 1 and 2, each contain two homogeneous and hybrid sections, while group 3 contains two hybrid cellular beams. Steel grades of S275 and S355 were used for the homogeneous sections, while for hybrid sections, both S355 and S275 were used for the upper and lower Tee parts, respectively. The results of group 2 indicate that the use of hybrid cellular beams can be more efficient in terms of load-carrying capacity when compared to homogeneous cellular beams. However, results showed that the failure mechanism and load-carrying capacity of cellular beams were mainly governed by the upper Tee part and section class. Hence, in some cases, it was observed that the use of a higher steel grade affected the failure mechanism and thus degraded the resistance capacity of the section due to section classification effects.
Keywords: Cellular beams; Hybrid; Homogeneous; Hot-rolled; Lateral-torsional buckling; Web buckling due to compression